2009
DOI: 10.1002/pmic.200800445
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of tandem affinity purified 14‐3‐3 protein complexes inArabidopsis thaliana

Abstract: In eukaryotes, 14-3-3 dimers regulate hundreds of functionally diverse proteins (clients), typically in phosphorylation-dependent interactions. To uncover new clients, a 14-3-3 omega (At1g78300) from Arabidopsis was engineered with a “tandem affinity purification” (TAP) tag and expressed in transgenic plants. Purified complexes were analyzed by tandem mass spectrometry. Results indicate that 14-3-3 omega can dimerize with at least 10 of the 12 14-3-3 isoforms expressed in Arabidopsis. The identification here o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 83 publications
(85 reference statements)
8
155
0
Order By: Relevance
“…There are many other examples of wRKY-MAP kinase interactions (Chi et al 2013). Other interacting partners of wRKY proteins include 14-3-3 proteins (Chang et al 2009), chromatin remodeling proteins such as Arabidopsis histone deacetylase 19 (Kim et al 2010), vQ proteins ), CC-NBR-LRR-type R proteins (Shen et al 2007), e3 ubiquitin ligases (Miao and Zentgraf 2010) and the chloroplast ⁄ plastid-localized ABA receptor, ABAR (Shang et al 2010). These interacting partners of wRKY TFs are providing increasing information as to the roles and mechanisms involved in wRKY TF action at the systems level.…”
Section: Interactomicsmentioning
confidence: 99%
“…There are many other examples of wRKY-MAP kinase interactions (Chi et al 2013). Other interacting partners of wRKY proteins include 14-3-3 proteins (Chang et al 2009), chromatin remodeling proteins such as Arabidopsis histone deacetylase 19 (Kim et al 2010), vQ proteins ), CC-NBR-LRR-type R proteins (Shen et al 2007), e3 ubiquitin ligases (Miao and Zentgraf 2010) and the chloroplast ⁄ plastid-localized ABA receptor, ABAR (Shang et al 2010). These interacting partners of wRKY TFs are providing increasing information as to the roles and mechanisms involved in wRKY TF action at the systems level.…”
Section: Interactomicsmentioning
confidence: 99%
“…In plants, in addition to the plasma membrane transport through the regulation of the H þ -ATPase activity, 14-3-3s are involved in the control of gene expression, in the cellular trafficking, in the control of the activities of diverse enzymes of metabolism, in the hormone signaling, and in general in the coordination of different signal transduction pathways (Aducci et al, 2002;Sottocornola et al, 2006;Camoni et al, 2011;Schoonheim et al, 2009;Denison et al, 2011). Lots of evidence suggest also a role of 14-3-3s in the plant response to stress conditions (G€ okirmak et al, 2010): environmental and biotic stresses can affect the expression levels of 14-3-3 genes (Chevalier et al, 2009) and also a large number of stresserelated proteins have been identified as 14-3-3 clients (Chang et al, 2009). Recently the involvement of 14-3-3 proteins in the plant response to salinity has been clear demonstrated for two 14-3-3 Arabidopsis isoforms that have been reported to regulate the Salt Overly Sensitive pathway, known to control sodium homeostasis during salt stress (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest the possibility that ATL31 regulates the function of 14-3-3 client proteins, which are localized at the plasma membrane, via 14-3-3 protein degradation in C/N-nutrient response. 14-3-3 proteins directly target plasma membrane-localized proteins, such as plasma membrane H ϩ -ATPase, phototropin receptor kinase, or putative glutamate receptor (57)(58)(59). Essential proteins involved in nutrient response, including receptors, transporters, and membrane trafficking factors, are localized at the plasma membrane, although their relationships with 14-3-3 proteins remain unclear.…”
mentioning
confidence: 99%